A phase I/II study of weekly high‐dose erlotinib in previously treated patients with nonsmall cell lung cancer - Milton, Daniel T.; Azzoli, Christopher G.; Heelan, Robert T.; Venkatraman, Ennapadam; Gomez, Jorge E.; Kris, Mark G.; Krug, Lee M.; Pao, William; Rizvi, Naiyer A.; Dunne, Megan; Miller, Vincent A. (Cancer, 2006)
BACKGROUND. Preclinical studies have suggested that erlotinib at high doses may inhibit additional sites downstream of the epidermal growth factor receptor (EGFR), resulting in greater antitumor efficacy. The objective of this study was to determine the tolerability and efficacy of high‐dose erlotinib administered on a weekly schedule to patients with advanced nonsmall cell lung cancer (NSCLC). METHODS. The authors conducted a Phase I/II trial of weekly erlotinib in patients with progressive NSCLC who had received previous chemotherapy. In the Phase I portion, patients were enrolled in 3‐patient cohorts at erlotinib dose levels of 1200 mg, 1600 mg, and 2000 mg once weekly. The Phase II portion was designed to determine the major objective response rate of the dose identified in the Phase I portion of the trial. RESULTS. Twenty‐seven patients were enrolled. No dose‐limiting toxicity was observed. Grade 1 and 2 rash and diarrhea were the principle toxicities, and each occurred in 92% of patients. Among 21 patients who were treated at the Phase II dose of 2000 mg weekly, a single objective response was identified, yielding a response rate of 5% (95% confidence interval, 0.2–22%). For this cohort, the median survival was 9.5 months. The sole radiographic response occurred in a patient whose pretreatment tumor specimen harbored an EGFR exon 19 deletion. CONCLUSIONS. Erlotinib at a dose of 2000 mg administered weekly was tolerated well by these patients with advanced NSCLC. The 5% objective response rate did not reach the stated objective at the interim efficacy analysis, prompting the closure of the study. Cancer 2006. © 2006 American Cancer Society. The epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors represent an important advance in the treatment of nonsmall cell lung carcinoma (NSCLC), but many patients who are treated with these agents do not benefit from their use. In an attempt to overcome resistance to EGFR tyrosine kinase inhibition, the authors of the current study administered high‐dose, oral erlotinib on a weekly schedule to determine the safety and efficacy in patients with advanced NSCLC.